OPTIMALISASI PEMAHAMAN FIKIH JAMAAH MASJID AL-IKHLAS MELALUI KAJIAN KITAB FATHUL QARIB - sugito, sugito; Khoirin, Lukman; faizin, khoirul; mahsun, moch (LP2M Institut Agama Islam Ngawi, 2025)
Islamic scholarly studies based on classical texts play a vital role in strengthening the religious literacy of Muslim communities. Fathul Qarib by Ibnu Qasim al-Ghazzi is frequently used as a foundational reference in Shafi'i jurisprudence. Masjid Al-Ikhlas consistently organizes study sessions of this book every Tuesday night. These sessions serve as a non-formal educational platform widely attended by people of various age groups. This study aims to analyze the effectiveness and impact of the sessions on the community’s understanding of fiqh. A qualitative case study approach was used. Data were collected through participant observation, in-depth interviews with five key informants, and structured questionnaires distributed to thirty regular attendees. The findings reveal a significant improvement in participants’ basic understanding of Shafi'i fiqh. Attendees demonstrated enhanced comprehension of religious practices such as ablution, prayer, and fasting. Most respondents reported behavioral changes in their daily worship practices. Social interactions among participants also improved. These sessions contributed to strengthening community cohesion and promoted a participatory culture of religious learning. The mosque functions as an active and relevant center for Islamic education. The results of this study emphasize the urgency of developing more interactive fiqh teaching methods to further enhance participant understanding and expand the reach and benefits of the study sessions.